Diaphragmatic ultrasound: A clinical perspective on diaphragm function in the ICU: Diaphragmatic ultrasound in critical care - Tangkitkiatkul, Nonpisit; Assavapokee, Taweevat (Clinical Critical Care, 2025)
Mechanical ventilation (MV) is a critical component in managing respiratory failure in critically ill patients. While lifesaving, prolonged MV can induce ventilator-induced diaphragmatic dysfunction (VIDD), characterized by decreased diaphragmatic function, atrophy, and loss of contractility. These complications exacerbate weaning challenges, extend ICU stays, and escalate mortality rates. Diaphragmatic ultrasound (DUS) offers a non-invasive, real-time evaluation tool that has revolutionized the monitoring and management of diaphragm function. This review delves into the pathophysiology of VIDD, evaluates its clinical impacts, and the integral role of DUS in implementing protective ventilation strategies to optimize outcomes for both lung and diaphragm health.